Thrombotic thrombocytopenic purpura: MR findings. - Tardy, B; Page, Y; Convers, P; Mismetti, P; Barral, F; Bertrand, J C (American Journal of Neuroradiology, 1993)
Neurologic manifestations occur in over 90% of patients with thrombotic thrombocytopenic purpura. Neuropathologically, thrombi produce occlusion of terminal arterioles and capillaries resulting in diffuse small infarcts. In the great majority of surviving patients, brain CT does not disclose any abnormalities. The authors report a case of thrombotic thrombocytopenic purpura in which brain MR examination showed multiple punctate lesions in the white matter.